Skills of Posyandu Cadres in the Use of Standardized Anthropometric Instruments in Gorontalo Regency - Mutia Reski Amalia; Mohamad Anas Anasiru; Indra Domili; Nuryani Nuryani; Imran Tumenggung; Ayu Bulan Febry Kurnia Dewi; Erni Mansyur; Shinto Mohamad; Maya Kumalasari Sugiyanto (Jurnal Keperawatan Profesional (KEPO), 2026)
Stunting remained a major public health problem in Indonesia, requiring accurate growth monitoring at integrated health service posts (Posyandu). Posyandu cadres played a vital role in performing anthropometric measurements to determine children’s nutritional status; however, measurement accuracy was often affected by limited technical competence. This study aimed to assess the knowledge and skills of Posyandu cadres in using standardized anthropometric tools in Gorontalo Regency. A mixed methods study was conducted using focus group discussions and a cross-sectional design. A total of 56 cadres were selected through proportionate stratified random sampling. Data were collected using structured questionnaires, observation checklists, and comparison with gold standard measurements. The results showed that 71% of cadres had good knowledge, but only 27% demonstrated adequate skills, and 21% correctly followed standard measurement procedures. The mean differences between cadre measurements and the gold standard were +0.03 kg for body weight and −0.21 cm for height/length. Limited training and lack of calibrated equipment were identified as key barriers. Improving regular training and ensuring the availability of standardized tools are essential to enhance measurement accuracy and support effective stunting prevention programs in primary healthcare settings.